Historische und religiöse Erzählungen - Borgmann, Nils (Germania litteraria mediaevalis francigena, 2014)
GLMF IV is devoted to historical and religious narratives of various origins adapted from the French, including German and Dutch historical epics based on ancient romances about Alexander, Aeneas, Troy (Part A), the historical epic based on Chansons de geste in five epic cycles (Part B), and shorter German religious narratives, such as Hartmann's ""Gregorius"" (Part C)